Streaming de jogos como sistema de performances : um olhar sobre a transmissão ao vivo de uma streamer de Fortnite através da Twitch - Dallegrave, Letícia (2020)
This research observes how the act of transmitting digital games online is formed by a set of simultaneous performances between game, player, platform and audience to create a form of live entertainment. For this, there is a conceptual rescue on performance with the proper contextualization in this environment, followed by the discussion on this behavior that unites playing and watching through the mediation of a platform. The research carried out a Case Study (YIN, 2010) of the content producer Loeya, known for presenting Fortnite matches on her channel on the platform Twitch. The gameplay is changed when shared and the player's role becomes multiple, as he is also a streamer. The audience has an agency and changes from spectator to coparticipant, if desired. The platform, directly and indirectly, influences live performance. The digital game works as a performance tool and provides context for the transmitted actions.